God, Hierarchy, and Power : Orthodox Theologies of Authority from Byzantium - Purpura, Ashley M. (Book collections on Project MUSE., 2018)
Presents an interpretation of power and authority in the Orthodox Christian theological tradition by examining four Byzantine authors on the topic of ecclesiastical hierarchy in theoretical, ritual, and pragmatic contexts. Discusses potential application of the interpretation for 21st century scholars and ecclesial participants.